Fudge-a-mania - Blume, Judy. (New York : Dell, 1990)
Pete describes the family vacation in Maine with the Tubmans, highlighted by the antics of his younger brother Fudge.
A Yearling book.
Keywords: Vacations -- Fiction; Brothers -- Fiction; Families -- Fiction; Humorous stories